A CAM controlled machine, one step to make machining as easy as printing - Didonato, A.; Reader, L.; Marin, J.; Naksangchun, N.; Nguyen, D. N.; Vignat, F. (Applied Science and Engineering Progress, 2013)
Manufacturing parts using a CNC machine needs highly skilled people. The development of new, user friendly human machine interfaces should make machining a designed part to be as simple as printing a document. A step towards this goal is to integrate CAM Software and CNC Machine controllers. The project aims to develop a new type of milling machine to simplify the stages between the design stage in CAD software and the manufacture of the designed part using the CNC machine. The solution chosen to achieve this is to integrate the CAM software, for this project the software is ESPRIT, with the CNC controller of the CNC machine. This project is a student project launched within the framework of an international semester project (Responsible Design) by a team of 4 students coming from all over the world